Obstacles to providing special education services for students with special needs in Palestinian public primary schools (Journal of the College of Basic Education, 2026)
Objectives: This study aims to identify the obstacles to providing special education services to students with special needs in basic public schools in Palestine.Methodology: The study used the descriptive-analytical approach, and the study sample consisted of (60) male and female special education teachers in the Nablus governorate.in the Tubas and Northern Valleys governorate, who were selected using a stratified random sampling method to ensure balanced representation across various academic specializations.Results: The study's findings reveal significant administrative obstacles in providing special education services. The most prominent of these are the absence of ministry-approved diagnostic tools, a lack of clarity regarding the special education teacher's duties, limited financial allocations, and an ambiguous future vision for the programs.The results also indicate medium to significant obstacles related to teachers, most notably a lack of communication skills, feelings of frustration, and a high teaching load. A weakness in training programs and collaboration between special and general education teachers was also observed. School environmental barriers were classified as significant obstacles, The most important of which is the lack of equipped classrooms., a shortage of technical, cultural, and academic resources, and a poor recreational and nutritional environment within the school.Conclusion: It is essential to adopt standardized diagnostic tools and tests from the Ministry of Education to accurately measure special educational needs. A clear organizational mechanism is needed to define the special education teacher's duties and teaching load, and to document them in official instructions. Finally, increased financial support for special education programs, from both the ministry and through community partnerships, is crucial.